Selenium and Human Health 2023
DOI: 10.5772/intechopen.110294
|View full text |Cite
|
Sign up to set email alerts
|

Photic Stress and Rhythmic Physiological Processes: Roles of Selenium as a Chronobiotic

Abstract: Physiological processes exhibit distinct rhythmic patterns influenced by external cues. External cues such as photic signal play an important role in the synchronization of physiological rhythms. However, excess of or indiscriminate exposure to photic signals exerts profound effects on physiological processes, disrupting normal hormonal secretory rhythms, altering sleep/wakefulness cycle, and impairing reproductive function. Alteration in sleep/wakefulness cycle, impairment in reproductive cycle, and disruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Peripheral oxygen saturation and shock index indicate level of tissue perfusion. Peripheral oxygen saturation is a proportion of oxygenated blood and it is influenced by capillary density [21,[36][37][38][39][40]. The study showed that post-exercise orthostasis elicited a decrease in peripheral oxygen saturation in males when compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral oxygen saturation and shock index indicate level of tissue perfusion. Peripheral oxygen saturation is a proportion of oxygenated blood and it is influenced by capillary density [21,[36][37][38][39][40]. The study showed that post-exercise orthostasis elicited a decrease in peripheral oxygen saturation in males when compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…It can also disrupt circadian rhythms, causing deranged melatonin secretion, altered leptin secretion, impaired hormonal secretions and altered sleep/wakefulness cycle [44][45][46][47]. Noise can cause headache, confusion, increase in blood pressure and heart rate [3,17,[48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…They are approved by the FDA for the treatment of solid tumors like breast, ovarian, lung, bladder, or prostate cancer and hematopoietic malignancies like leukemia and lymphoma, respectively. [11][12][13] The significance of such biologicals is highlighted by the fact that around 25% of all pharmaceutical drugs are either natural products or derived from such substances. 8 Plumbagin (5-hydroxy-2-methyl-1,4-naphthoquinone) is a secondary metabolite found in plants of the Plumbaginaceae family (Plumbago capensis, Plumbago rosea, and Plumbago indica).…”
Section: Introductionmentioning
confidence: 99%